"Sediment capacitors" help explain debris flow events. (12th November 2013) - Balcerak, Ernie
<x xml:space="preserve">Abstract</x> Runoff during rainstorms plays a key role in initiating many debris flow events, but exactly how these debris flow events begin is not well understood. To better understand how debris flows are initiated by runoff, Kean et al. monitored both the triggering rainfall and the associated debris flow at two small catchments: a bedrock‐dominated alpine basin in central Colorado and a recently burned area in southern California. They also studied video footage from cameras at the Colorado site.